Auricular shell reconstruction with retroauricular - mastoid flap,about a case - Palacios Martínez, Jorge; Almeida Betty, Cristina; Mariscal Tapia, Freddy (Revista Universidad de Guayaquil, 2015)
We have made a detailed description of the technique of the retroauricular — mastoid flap as an alternative choice for the reconstruction of auricular shell. As the defect is caused by the excision of the injury, we can choose the width and thickness of the flap which will bring cover to this defect. For the selection of the vascular pedicle, respective pre — marking is made.The report of this case has been conducted using data from a patient in the private practice, with a tumorof 2 cm diameter, and one month of evolution, located in the anterior aspect of the auricular shell. Such cases are frequent in the area of consultation, allowing us to keep better tracing of it, with histopathological diagnosis and post — surgical checks.
Keywords: shell; flap; retroauricular; mastoid; tumor